Improving the strength capabilities of qualified female weightlifters in the preparatory period of the annual training cycle - Misbakhov, A.A.; Usmanova, E.N.; Kozhanov, V.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study To develop practical recommendations for improving strength abilities, taking into account the nutrition and endocrine system performance of qualified female weightlifters. Methods and structure of the study. We conducted a pedagogical experiment involving six female weightlifting masters of sport and three amateur athletes. The study was conducted at the Batyr Sports Complex in Kazan. We studied performance in competitive events (snatch and clean and jerk) and results in control exercises for explosive strength. Results and conclusions. While studying the hormonal levels of female weightlifters during the preparatory period, we identified two types of hormonal imbalances: low triiodothyronine levels and high thyroxine levels. We developed a retracting microcycle for low triiodothyronine levels and high thyroxine levels. Improving strength abilities requires not only a well-designed training plan and high motivation, but also maintaining normal levels of endocrine hormones.